A Novel Subcutaneous Site of Islet Transplantation Superior to the Liver. Issue 6 (June 2018) - Yasunami, Yohichi; Nakafusa, Yuki; Nitta, Naoyoshi; Nakamura, Masafumi; Goto, Masafumi; Ono, Junko; Taniguchi, Masaru
Abstract : Background: Islet transplantation is an attractive treatment for patients with insulin-dependent diabetes mellitus, and currently, the liver is the favored transplantation site. However, an alternative site is desirable because of the low efficiency of hepatic transplantation, requiring 2 to 3 donors for a single recipient, and because the transplanted islets cannot be accessed or retrieved. Methods: We developed a novel procedure of islet transplantation to the inguinal subcutaneous white adipose tissue (ISWAT) of mice and described functional and morphological characteristics of transplanted syngeneic islets. Also, it was determined whether islet allograft rejection in the ISWAT can be prevented by immunosuppressive agents. Furthermore, it was examined whether human islets function when grafted in this particular site of immune-deficient mice. Results: In this site, transplanted islets are engrafted as clusters and function to reverse streptozotocin-induced diabetes in mice. Importantly, transplanted islets can be visualized by computed tomography and are easily retrievable, and allograft rejection is preventable by blockade of costimulatory signals. Of much importance, the efficiency of islet transplantation in this site is superior to the liver, in which hyperglycemia of diabetic recipient mice is ameliorated after transplantation of 200 syngeneic islets (the islet number yielded from 1 mouse pancreas) to the ISWAT but not to the liver. Furthermore, human islets transplanted in this particular site function to reverse diabetes in immune-deficient mice. Conclusions: Thus, the ISWAT is superior to the liver as the site of islet transplantation, which may lead to improved outcome of clinical islet transplantation. Abstract : The authors develop a novel procedure of islet transplantation to the inguinal subcutaneous white adipose tissue in a mouse diabetic model. The new site of islet transplantation demonstrates high efficiency of attenuating hyperglycemia. Supplemental digital content is available in the text.